Six new species of the planthopper genus Usana Distant, 1906 (Hemiptera: Fulgoromorpha: Achilidae) from China - Long, Jian-Kun; Yang, Lin; Chen, Xiang-Sheng (Zootaxa, 2015)
Six new species of the planthopper genus Usana, U. aspergilliformis sp. nov., U. concava sp. nov., U. congjiangensis sp. nov., U. fissura sp. nov., U. oblongincisa sp. nov. and U. unispina sp. nov. are described and illustrated from China. A checklist, a key to all species of the genus and illustrations of U. lineolalis Distant, 1906 are also given.